Analisis Minat Belajar Siswa pada Pembelajaran Matematika Kelas Virtual di SMA - Avianti Permata Yuniar; Syamsuri Syamsuri; Aan Hendrayana (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2021)
This study aims to obtain information on students' interest in learning on virtual classes in mathematics at SMA Negeri 1 Cikande. This type of research is quantitative with the research method used is descriptive method. The data collection technique used was a questionnaire. The research instrument used was a scale questionnaire of interest in learning mathematics. The population in this study were all students of SMA Negeri 1 Cikande, while the sample was class XI as many as 4 classes and XII as many as 5 classes totaling 233 students from 9 classes. The results obtained from this study indicate that student interest in learning mathematics virtual classes on four indicators, namely; 37.77% of students felt happy, 42.49% of students were interested in learning, 42.06% of students were involved in learning, and 47.21% of students showed attention into the learning. These results indicate that the interest in learning mathematics in mathematics learning in virtual classes needs to be increased.